“Four years of ramen and poverty:” using participatory research to examine food insecurity among college students at Kansas State University - Klugesherz, Miranda Blaise (Kansas State University, 2017)
Defined by the U.S. Department of Agriculture as “limited or uncertain availability of nutritionally adequate and safe foods,” food insecurity is a symptom of systematic disempowerment and represents one of the most prevalent social ailments to impact first-world countries. In a county where one in eight individuals does not have regular access to meals, food insecurity is far from a problem typically associated with college students. However, Feeding America, the largest emergency food assistance network in the nation, reports that one out of every ten people they serve is a student. In total, half of all students will find themselves unable to afford to eat at least once within their academic career; consequently, 1 in 4 will drop out. This thesis argues that the voices and narratives of food insecure students have been absent from the very research meant to represent them. Consequently, little is known of the situational nuances that accompany student hunger, reifying the dominant discursive structure. This research employs Photovoice, a participant-led methodology which invites members of marginalized groups to photograph places, things, and events representative of, or crucial to, their daily life. This study examines the narratives of seven college students, ranging from their first-year to PhD status, in an effort to fill the gap in the knowledge regarding student hunger and food insecurity. This research found that students who experience food insecurity engage in self-blaming practices and, thus, do not believe they have the right to be hungry or ask for help. Instead, food-insecure students employ several strategies, including face negotiation and disclosure, to minimize the severity of their situation and mitigate tensions between their health, finances, and convenience. This study concludes with a discussion of implications, limitations and areas for future research.
Keywords: Phenomenology; Narrative; Participatory researchFood insecurity; Photovoice